Molecular dynamics simulation of palm kernel oil esters-based nano-emulsion with ibuprofen and dipalmitoylphosphatidyl-choline lipid bilayer - Faujan, Nur Hana (2016)
Transdermal drug delivery shows a great potential to enhance the permeation process of drugs with poor solubility and low degree of bioavailability. Nevertheless, the penetration of drug through the skin is a big challenge to overcome. Nano-emulsion system can offer the solution to this problem by acting as chemical penetration enhancers (CPEs). Therefore, palm kernel oil esters (PKOEs)-based and oleyl laurate (OLA)-based nano-emulsion systems were used as drug carrier model. PKOEs-based nano-emulsions with ibuprofen (PKOEs:IBU/T80) and without ibuprofen (PKOEs/T80) were simulated followed by the simulation with dipalmitoylphosphatidylcholine (DPPC) in water (PKOEs/DPPC). The PKOEs/T80, PKOEs:IBU/T80 and PKOEs/DPPC were simulated to determine the effect of surfactant and drug in the model systems. All simulations were performed using all-atom level molecular dynamics (MD) technique for 50 ns. The aggregation process was observed rapidly in the PKOEs-based nano-emulsion systems. These simulations provided better understanding and insight onto the properties of esters, surfactants, drug and water as well as the diffusion of IBU in PKOEs-based nano-emulsion system. A prolate ellipsoidal shape was obtained in both PKOEs/T80 and PKOEs:IBU/T80 models whereas a doughnut-like toroidal shape was gained in PKOEs/DPPC system. The average radius of gyration (Rg) values of 4.43 (±0.01), 4.50 (±0.00) and 4.09 (±0.01) nm were reported for the PKOEs/T80, PKOEs:IBU/T80 and PKOEs/DPPC aggregates, respectively. The radial distribution function (RDF) analysis detected higher interaction between the PKOEs molecules compared to surfactant molecules in all models which could be due to the hydrophobic interaction in the aggregated structures. In addition, oleyl oleate (OLE) produced the strongest interaction between IBU molecules with the RDF value of 1.26 (±0.41) in the PKOEs:IBU/T80 aggregate. Oleyl laurate was used as the main composition of PKOEs for coarse-grained molecular dynamics (CG-MD) simulation study. CG-MD simulation was applied to investigate the aggregation process of OLA-based nano-emulsion with IBU (OLA:IBU/T80) and without IBU (OLA/T80) for 500 ns. The structure of the OLA/T80 and OLA:IBU/T80 aggregates were not completely spherical. The Rg values obtained were 4.36 (±0.04) and 4.34 (±0.04) nm, respectively. The distribution of IBU molecules between the OLA was higher compared to T80 molecules in OLA:IBU/T80 model with the RDF values of 1.77 (±1.16) and 1.12 (±0.40), respectively. The OLA:IBU/T80 was then simulated with DPPC as a lipid bilayer model. The new model created provided a detailed understanding of the diffusion process of drug through the skin. The OLA:IBU/T80 aggregate was able to move freely inside DPPC molecules. The diffusion of OLA:IBU/T80 also affected the DPPC lipid bilayer structure by disturbing the structure of DPPC and losing the bilayer compactness during 500 ns. The RDF value of DPPC as a lipid bilayer model was decreased from g(r)=2.92 to g(r)=1.22 in the presence of OLA:IBU/T80 aggregate.